Mechanobiological and neuromuscular responses to foot-position variations during front and back squat exercises - Bozkurt, Ömer; Erdağ, Deniz; Tinazci, Cevdet; Burgul, Nazım; Bekiroğulları, Hasan (Frontiers in Physiology, 2026)
IntroductionThis study investigated the mechanobiological and neuromuscular effects of three foot-position techniques—flat heel (FH), heel-elevated (HE), and forefoot-elevated (FE)—during front and back squat exercises. Variations in foot positioning were expected to influence muscle activation, joint kinematics, ground reaction forces, and postural stability.MethodsTwelve resistance-trained male athletes (mean age 23.4 ± 3.8 years; training experience 8.1 ± 2.7 years) performed squats at 70% of their one-repetition maximum (1RM) under each foot-position condition. Surface electromyography (EMG) assessed lower-limb muscle activation, while joint angles and ground reaction forces were collected through synchronized motion-capture and force-platform analyses. Measures included EMG amplitude, joint kinematics, ground reaction forces, and center-of-pressure (COP) displacement.ResultsQuadriceps muscles (vastus lateralis, vastus medialis, rectus femoris) showed significantly greater activation in FH and HE compared with FE (p < 0.001), particularly during the ascent phase. Heel-elevated increased ankle dorsiflexion and squat depth, whereas FE reduced vertical ground reaction forces and shifted mechanical loading toward the posterior chain. No significant differences were observed in COPx or COPy across conditions.DiscussionFoot-position variations meaningfully altered mechanical load distribution and neuromuscular activation patterns, demonstrating human-scale mechanotransduction. The findings suggest that technique selection should be tailored to individual mobility, joint mechanics, and performance goals to optimize training outcomes and reduce injury risk.